The Influence of MSME Perceptions of Accounting on The Use of Accounting Information - Ulva Rizky Mulyani (Monex: Journal of Accounting Research, 2022)
The purpose of this research is to examine the influence MSME actors' perceptions of accounting, accounting knowledge, business experience on the use of accounting information. The population in this study is a MSMEs in Kudus Regency. The sample selection is conducted by using simple random sampling method and obtained samples are 63 MSME in Kudus Regency. The analysis method of this study was structural equation model using Partial Least Square (PLS) software. The result of this research shows MSME actors' perceptions of accounting and accounting knowledge have no significant to use of accounting information. Business experience has positive significant influence to use of accounting information. Keyword: MSME actors' perceptions of accounting, accounting knowledge, business experience, use of accounting information